Pneumonectomy in Isoflurane-Anesthetized Rats without Tracheal Intubation: An Experimental Model - Rombolá, C. A.; Tagliaferri, E. M.; Boué, A. A.; García-Jiménez, M. D.; Picazo, M. G.; García-Olmo, D. C. (The Thoracic and Cardiovascular Surgeon, 2014)
Introduction A few models for pneumonectomy in rats have been described, and in most of these, anesthesia includes orotracheal intubation, which increases morbidity and mortality and also adds technical complexity. Models without tracheal intubation but with injectable anesthesia are difficult to reproduce, however, and lead to a lengthy postoperative-recovery period with high morbidity and mortality rates.Objective The objective of this study was to describe a simple, safe, and effective experimental model for pneumonectomy in rats without tracheal intubation.Materials and Methods A left-sided pneumonectomy was performed on 26 Sprague-Dawley rats anesthetized by isoflurane applied via a mask without tracheal intubation. To avoid dangerous traction movements, the lung pedicle was ligated en bloc using clips.Results and Discussion No rat demonstrated cardiorespiratory depression. Of the 26 rats, 1 was dehydrated and had lost more than 10% of its body weight, resulting in death on the third day after surgery. Total mortality was therefore 3.8%. Mean (standard deviation [SD]) anesthesia duration was 9.8 (1.0) minutes, surgery time was 3.0 (0.6) minutes, and open pneumothorax time was 1.2 (0.3) minutes. Mean (SD) weight loss during the early postoperative period was 4.5% (3.5%). These results were more satisfactory than results obtained using ketamine mixtures as anesthetic agents (ketamine plus xylacine, and ketamine plus diazepam).Conclusion Our model for left-sided pneumonectomy in isoflurane-anesthetized rats does not require endotracheal intubation and is effective, safe, quick, and easily reproducible.
Keywords: pneumonectomy; rats; isoflurane